2015
DOI: 10.5539/ass.v11n5p97
|View full text |Cite
|
Sign up to set email alerts
|

Conceptual Framework: AIS Technostress and Its Effect on Professionals’ Job Outcomes

Abstract: The purpose of this paper is to develop a conceptual framework that examines and provides a systematic understanding of the impact of accounting information system (AIS) information characteristics on technostress creators and its effect on professionals' job outcomes. The research draws on literature in technostress, AIS information characteristics, job satisfaction, task performance and social psychology in order to ascertain the impact of AIS information characteristics on technostress creators and its effe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 36 publications
0
11
2
Order By: Relevance
“…The inducement of the chaos theory in explaining the ICT users' behavior is not deniable. The authors demonstrate the chaotic behavior from two sides, which are complex interactions and the collaboration of the ICT system's elements [5][6][7][8][9][10][11][12][13][14][15][16][17][18], and both defacement [22] and iconoclastic methods [23]. These two sides affect ICT users' behavior when they have to face the technostress's creators.…”
Section: Inducing the Chaos Theory To Explain Behavioral Phenomenamentioning
confidence: 99%
See 1 more Smart Citation
“…The inducement of the chaos theory in explaining the ICT users' behavior is not deniable. The authors demonstrate the chaotic behavior from two sides, which are complex interactions and the collaboration of the ICT system's elements [5][6][7][8][9][10][11][12][13][14][15][16][17][18], and both defacement [22] and iconoclastic methods [23]. These two sides affect ICT users' behavior when they have to face the technostress's creators.…”
Section: Inducing the Chaos Theory To Explain Behavioral Phenomenamentioning
confidence: 99%
“…In this condition, if the users cannot adapt to this technological progress and complexity, they will feel frustrated and depressed, experiencing what is called technostress. Then, this technostress will have an impact on decreasing the users' satisfaction with this ICT [5][6][7][8][9][10][11][12], their performance [5,[13][14][15], productivity [16][17][18], innovation [12,13], commitment to the organization [11,12], and role conflicts [12,16]. They could survive in these chaotic conditions if their organizations facilitate the users with flexibility and adaptability in the ICT systems [19].…”
Section: Introductionmentioning
confidence: 99%
“…However, many papers have studied financial reporting in terms of the effectiveness consequences of the managerial and financial reporting system, such as Stocken and Verrecchia (2004), while other researchers have studied the reporting systems in terms of the characteristics of its output (broad scope, timeliness, aggregation, and integration), such as the paper of Saganuwan, Ismail, and Ahmad (2015), Irawati and Ardianshah (2018).…”
Section: Introductionmentioning
confidence: 99%
“…According to Blaug, Kenyon and Lekhi (2007) people experiences workplace stress when there is an imbalance between performance expectations and resources and employee's capabilities to meet that expected performance, [10]. Another study showed that technological use at workplace has added to the occupational stress levels of employees.…”
Section: Technostress and Its Effects On Human Healthmentioning
confidence: 99%
“…Another definition given by Brod (1984) is, "Technostress (computer related stress) is a combination of performance anxiety, information overload, role conflicts and organizational actors", [1]. Technostress is also metaphorically stated as an 'offspring of stress' [10].…”
Section: Technostress and Its Effects On Human Healthmentioning
confidence: 99%